In these lessons, we will look at the distributive property and how it can be used to solve algebraic equations.

Related Topics: More Algebra Lessons

### Distributive Property

The distributive property of addition and multiplication states that multiplying a sum by a number is the same as multiplying each addend by that number and then adding the two products. For example, 3(2 + 4) = (3 *•* 2) + (3 *•* 4)

The following video shows some examples of the distributive property.
Using the distributive property in algebra.

### Solving Equations using Distributive Property

The following video shows some examples of solving multi-step equation by distributive property and combine like terms.
Solving Equations with the Distributive Property

Solving equations with the distributive property 2

You can use the free Mathway widget below to practice Algebra or other math topics. Try the given examples, or type in your own problem and check your answer with the step-by-step explanations.

Related Topics: More Algebra Lessons

The following video shows some examples of the distributive property.

To solve algebra equations using the distributive property, we need to distribute (or multiply) the number with each term in the expression. In that way, the brackets are removed. We can then combine like terms and solve by equivalent equations when necessary.

Remember to apply the following rules for sign multiplication when necessary.

** Rules for sign multiplication: **

(+) • (+) = (+)

(+) • (–) = (–)

(–) • (+) = (–)

(–) • (–) = (+)

** Example: **

Solve
3(2*x* + 5) = 3

*Solution: *

[3 *• *2*x*] + [3 *• *5] = 3 (use distributive property)

6*x* + 15 = 3 (subtract 15 from both sides)

6*x* = –12 (divide 6 on both sides)

* x* = –2

* Check: *

3(2x + 5) = 3 (substitute x = –2 into the original equation)

3((2 • –2) + 5) = 3

* Example: *

Solve
2*x* – 2(3*x* – 2) = 2(*x* –2) + 20

* Solution: *

2*x* – 2(3*x* – 2) = 2(*x* –2) + 20

2*x* – 6*x* + 4 = 2*x* – 4 + 20 (use distributive property)

– 4*x* + 4 = 2*x* + 16 (combine like terms)

–4*x* + 4 – 4 –2*x* = 2*x* + 16 – 4 –2*x* (add or subtract on both sides)

–6*x* = 12 (divide both sides by –6)

*x* = –2

* Check: *

2*x* – 2(3*x* – 2) = 2(*x* –2) + 20 (substitute x = –2 into the original equation)

(2 • –2) – 2((3 • –2) –2) = 2(–2 –2) + 20

12 = 12Solving equations with the distributive property 2

Rotate to landscape screen format on a mobile phone or small tablet to use the **Mathway** widget, a free math problem solver that **answers your questions with step-by-step explanations**.

You can use the free Mathway widget below to practice Algebra or other math topics. Try the given examples, or type in your own problem and check your answer with the step-by-step explanations.

We welcome your feedback, comments and questions about this site or page. Please submit your feedback or enquiries via our Feedback page.